Gram Typing: Gram‐Typing Using Conjugated Oligoelectrolytes (Adv. Funct. Mater. 42/2020). (16th October 2020) - Zhou, Cheng; Ho, James C. S.; Chia, Geraldine W. N.; Moreland, Alex S.; Ruan, Lin; Liedberg, Bo; Kjelleberg, Staffan; Hinks, Jamie; Bazan, Guillermo C.
Abstract : In article number 2004068, Jamie Hinks, Guillermo C. Bazan, and co‐workers develop a membrane‐specific fluorescent dye that selectively stains Gram‐positive bacteria based on a conjugated oligoelectrolyte molecular structure. The conjugated oligoelectrolyte does not exhibit antimicrobial characteristics and enables in‐situ visualization of individual Gram types in bacterial mixtures, including polymicrobial biofilms. The characterization methods are simple to implement and may be used in different formats, including confocal microscopy and visual inspection.